Viabilidad para la Constitución de una Empresa para Importar Piñatex desde España para Elaborar y Comercializar Calzado en Bogotá, Colombia - Bulla Jiménez, Michael Giovanny; Liquitan Calambas, Kimberly Natalia (Universidad Antonio Nariño, 2024)
This project is focused on the constitution of a company dedicated to the import of vegetable leather from Spain; being the country where it is distributed internationally. This leather is made from the fiber of pineapple leaves, called “Piñatex”. Being distinguished in the international market, because it is an innovative alternative, which replaces tannery leather.